The law's universal condemning and enslaving power : reading Paul, the Old Testament, and second temple Jewish literature - Blazosky, Bryan, 1983- (Bulletin for biblical research supplements, 2019)
"Explores Paul's view of the Mosaic law's relationship to Gentile Christians, and explores the logic of Paul's approach, comparing his view on this issue to views found in the Old Testament and Second Temple Jewish literature"--Provided by publisher